2020
DOI: 10.32457/ijmss.v7i1.479
|View full text |Cite
|
Sign up to set email alerts
|

Human anatomical dissection takes a compulsory break during Covid-19 pandemic

Abstract: The outbreak of the coronavirus effects on people’s daily lives. Like nothing most people have experienced before, one of the many affected sectors is education. In response to Covid-19 pandemic, medical education faculty have quickly transitioned the curriculum to online formats. But no matter the quality of the online resource, do not provide the same level of understanding of complex anatomical relationships as studying human bodies. Under restriction of social isolation because of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Recently, the Covid‐19 pandemic forced teachers and students to stay safe at home and learning human anatomy online. During this pandemic human anatomical dissection takes a compulsory break like most human activities (Romero‐Reveron, 2020). Therefore, the role of technological innovations in anatomical education was boosted, and the use of remote learning was implemented and further evaluated (Tekiner et al, 2020; Mateen & Kan, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Covid‐19 pandemic forced teachers and students to stay safe at home and learning human anatomy online. During this pandemic human anatomical dissection takes a compulsory break like most human activities (Romero‐Reveron, 2020). Therefore, the role of technological innovations in anatomical education was boosted, and the use of remote learning was implemented and further evaluated (Tekiner et al, 2020; Mateen & Kan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Here the authors, partially and respectfully disagree with Saverino's idea of how medical students should learn anatomy. Anatomical education builds the foundation for a safe, efficient, and effective medical practice and helps students, better than any other electronic or modern tool, to experience and understand the three‐dimensionally complex anatomical structures, their variation, and diversity (Brenner et al, 2003; Turney, 2007; Romero‐Reveron, 2020; Ross et al, 2021). Cadaveric dissection goes beyond the mere teaching of morphology: smells, touches and incisions cannot be simulated perfectly, making learning anatomy with virtual dissection unrealistic (Brassett et al, 2021; Onigbinde et al, 2021; Patra et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Students will come back to their essential training in medical sciences after the coronavirus pandemic runs its course (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to be on campuses resulted in medical education courses such as anatomy being moved from the traditional classroom environment to many forms of online teaching such as posting post‐edited videos online, live online interactions, and virtual learning platforms (Smith & Pawlina, 2021; Yan et al, 2021). The Covid‐19‐induced lockdown severely disrupted the dissection component of anatomy for medical students thereby calling for immediate implementation of alternative methods to deliver the cadaver dissection content (Romero‐Reverón, 2020; Naidoo et al, 2021). Two large surveys carried out among anatomy teachers in China revealed the relatively poor preparation for online learning in response to the unforeseen pandemic (Cheng et al, 2021; Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Conducting didactic online teaching without cadaver dissections has been challenging to both the students and teachers (Singal et al, 2021). Several studies from across the world have reported on the different experiences and challenges faced during the transition from traditional to Covid‐19‐induced virtual learning of anatomy (Longhurst et al, 2020; Romero‐Reverón, 2020; Khan et al, 2021; Lemay et al, 2021). Some studies reported smooth transition and successful use of information technologies to foster anatomy learning (Dulohery et al, 2021; Papapanou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%